Interpreting flow cytometry with caution: A case report of follicular lymphoma in leukemic phase misdiagnosed as chronic lymphocytic leukemia - Ren, Yuan; Jia, Congwei; Chen, Miao; Wang, Wei; Zhang, Wei (Frontiers in Oncology, 2023)
Chronic lymphocytic leukemia (CLL) is a subtype of mature B-cell proliferative neoplasms characterized by abnormally increasing lymphocytes in circulation. The diagnosis of CLL is usually established on peripheral blood analysis and typical flow cytometric immunophenotype rather than biopsy. In particular, the high RMH (Royal Marsden Hospital Scoring System for CLL) score of immunophenotype has a highly sensitive weight for diagnostic value. However, immunophenotyping by flow cytometry may also be misleading in specific clinical situations. Here we report a case on admission with lymphadenopathy and lymphocytosis, was misdiagnosed as chronic lymphocytic leukemia by flow cytometry initially but finally confirmed as follicular lymphoma (FL) in leukemic phase via lymph node biopsy. Since FL in leukemic phase is uncommon at the time of diagnosis and indicates a poorer prognosis of FL, such misdiagnosis is worthy of attention. And it is also thought-provoking about the phenomenon that there had conflicts between immunophenotype of bone marrow and immunohistochemistry of lymph node. Our case report aims to remind clinicians’ awareness that the immunophenotyping by flow cytometric analysis need to be interpreted with caution especially when the results cannot account for all of clinical features, and it is significant to make the right decision about when to conduct further examination including lymph node biopsy for avoiding misdiagnosis.